Costs and Resource Use Among Patients with Cervical Cancer, Cervical Intraepithelial Neoplasia, and Genital Warts in Algeria - Ali-Chakib Bennacef; Aomar Ammar Khodja; Fadl Allah Abou-Bekr; Tidiane Ndao; Ryan Holl; Goran Benčina (Journal of Health Economics and Outcomes Research)
**Background:** Cervical cancer rates in North Africa have risen in the last 10 years, suggesting that this region might benefit from cervical cancer screening and HPV vaccination programs. To assess the potential benefits of cervical cancer screening and HPV vaccination in North African countries, country-specific data on the prevalence and burden of HPV-related conditions are needed.